2018
DOI: 10.1039/c8nr03586e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interfacial mechanical–thermal characteristics of atomically thin two-dimensional crystals

Abstract: Owing to the flexible nanoelectronic applications of two-dimensional (2D) materials, further exploration of their nanoscale local mechanical properties and their coupled physical characteristics becomes extremely significant. The puckering effect is a typical micro/nanoscale local frictional characteristic generally in the tip-film-substrate system, which is simultaneously expected to be coupled with a dynamic thermal interfacial response. Here, applying scanning thermal microscopy (SThM), we observed a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Scanning thermal microscopy (SThM) [120,121] can quantitatively map temperature fields or thermal properties by scanning a sharp SThM probe with a temperature sensor at the tip. This technique has been applied in diverse areas, including microelectronics [122][123][124], optoelectronics [125,126], carbon nanotubes [127,128], and 2D material [53], since the 1990s.…”
Section: Scanning Thermal Microscope (Sthm)mentioning
confidence: 99%
See 2 more Smart Citations
“…Scanning thermal microscopy (SThM) [120,121] can quantitatively map temperature fields or thermal properties by scanning a sharp SThM probe with a temperature sensor at the tip. This technique has been applied in diverse areas, including microelectronics [122][123][124], optoelectronics [125,126], carbon nanotubes [127,128], and 2D material [53], since the 1990s.…”
Section: Scanning Thermal Microscope (Sthm)mentioning
confidence: 99%
“…The electric resistance of the probe is thermosensitive, and the relationship of the electric resistance (R probe ) versus temperature (∆T probe = T probe -T air ) is shown in figure 13(d). The maximum electric resistance is observed at 550 • C. Below 550 • C, the electric resistance of the probe corresponds to a specific temperature, as follows [53]:…”
Section: Scanning Thermal Microscope (Sthm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, the atomic force microscope (AFM) provides a multiphysical field coupling platform to probe the local mechanical, electronic, thermal, and other physical behavior on a nanoscale level. [10][11][12] The mechanical detection is especially sensitive to tuning the temperature-dependent structure and properties under an artificially controlled field.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomechanical deformation has been extensively investigated by the atomic force microscopy (AFM) indentation experiments on suspended films. [21][22][23] Based on AFM platform, [24][25][26][27] friction force microscopy (FFM) and transverse shear microscopy (TSM), as the derivative mode of contact AFM, [28][29][30][31][32] now have been widely used to study the elastic deformation, 19,31 crystal structure, 28 surficial ripples of 2D materials 8,34,35 and so on. Such studies have revealed an important phenomenon in which nanomechanical contact behavior could be dependent on the number of layers and substrates.…”
mentioning
confidence: 99%